Obesity inhibits the osteogenic differentiation of human adipose-derived stem cells. Issue 1 (December 2016) - Strong, Amy; Hunter, Ryan; Jones, Robert; Bowles, Annie; Dutreil, Maria; Gaupp, Dina; Hayes, Daniel; Gimble, Jeffrey; Levi, Benjamin; McNulty, Margaret; Bunnell, Bruce
Abstract Background Craniomaxillofacial defects secondary to trauma, tumor resection, or congenital malformations are frequent unmet challenges, due to suboptimal alloplastic options and limited autologous tissues such as bone. Significant advances have been made in the application of adipose-derived stem/stromal cells (ASCs) in the pre-clinical and clinical settings as a cell source for tissue engineering approaches. To fully realize the translational potential of ASCs, the identification of optimal donors for ASCs will ensure the successful implementation of these cells for tissue engineering approaches. In the current study, the impact of obesity on the osteogenic differentiation of ASCs was investigated. Methods ASCs isolated from lean donors (body mass index <25; lnASCs) and obese donors (body mass index >30; obASCs) were induced with osteogenic differentiation medium as monolayers in an estrogen-depleted culture system and on three-dimensional scaffolds. Critical size calvarial defects were generated in male nude mice and treated with scaffolds implanted with lnASCs or obASCs. Results lnASCs demonstrated enhanced osteogenic differentiation in monolayer culture system, on three-dimensional scaffolds, and for the treatment of calvarial defects, whereas obASCs were unable to induce similar levels of osteogenic differentiation in vitro and in vivo. Gene expression analysis of lnASCs and obASCs during osteogenic differentiation demonstrated higher levels of osteogenic genes in lnASCs compared to obASCs. Conclusion Collectively, these results indicate that obesity reduces the osteogenic differentiation capacity of ASCs such that they may have a limited suitability as a cell source for tissue engineering.